Estrategias clínicas para la detección temprana de cardiopatías congénitas críticas en atención primaria. - Balseca Artos, Eddy; Campoverde Loor, Carolina; Manzano Pérez, Johanna; Mallitasig Velasco, Bryan; Fiallos Brito, Edisson (Andes Pediatrica)
Early detection of critical congenital heart diseases is essential to reduce neonatal morbidity and mortality. At the primary care level, timely recognition of clinical warning signs, supported by tools such as pulse oximetry, allows for early referral and appropriate management. Objective: To describe strategies for the early identification and initial management of severe congenital heart diseases in newborns, aimed at primary healthcare professionals. Material and Method: Narrative review following the six domains of the Scale for the Assessment of Narrative Review Articles (SANRA) of the scientific literature published between 2015 and 2025, obtained from international databases. Clinical studies, clinical practice guidelines, and systematic reviews were selected based on their relevance and applicability to primary care settings. Results: Critical congenital heart diseases may present with respiratory distress, cyanosis, shock, and feeding intolerance. Diagnostic tools such as pulse oximetry and the hyperoxia test help differentiate cardiac from respiratory etiologies. Neonatal screening performed between 24 and 48 hours of life, complemented by a thorough physical examination, significantly improves early detection in resource-limited settings. Imaging studies may guide the differential diagnosis. Conclusions: Careful clinical assessment and the appropriate use of simple diagnostic tests are essential to reduce mortality associated with these heart conditions. Strengthening neonatal screening programs and training healthcare personnel should be considered a priority in primary care.